The Relationship of Students Learning Motivation with Biology Learning Outcomes for Class XI - Wini Mulya Wini; Siska Nerita; Liza Yulia Sari (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
Learning motivation is a condition that exists in a person where there is an urge to do something so as to achieve the desired goal. The purpose of study is to determine the relationship between learning motivation and learning outcomes of class XI biology at SMAN 2 Solok Selatan. This research is a correlation study with the student population of class XI SMAN 2 Solok Selatan. The instrument used in this research is a questionnaire with a Likert scale. The research data were analyzed using Pearson's Product Moment and then a t-test was perfomed to determine the correlation. The results showed that there was a significant relationship between learning motivation and the learning outcomes of class XI students during learning at SMAN 2 Solok Selatan. The conclusion of this study is that learning motivation affects learning outcomes.Keywords: Correlation; learning outcomes; motivation